3 tons pure electric vehicles power system design based on Cruise - Xinyu Liu; Houjie Tian (MATEC Web of Conferences, 2017)
The pure electric minivan is different from electric car. Combined with a given vehicle, vehicle simulation model established in Cruise software, complete simulation by setting tasks for the selected models designed drivetrain. Simulation results show that: The design of the transmission ratio can best meet the performance requirements of the matching target power analysis and simulation of electric minivan provides a new way, with practical guidance.